2013
DOI: 10.4236/health.2013.52025
|View full text |Cite
|
Sign up to set email alerts
|

A new category of “future planning” in the activity card sort: Continuity versus novelty in old age

Abstract: The Activity Card Sort (ACS) is a widely used measure for assessing participation in instrumental, leisure, and social-cultural activities. The ACS addresses previous and current activities but not future activity plans. The purpose of the study was to extend the ACS to include future planning. Previous research indicates that participation in activities and future planning is positively related to life satisfaction, and increased well-being and that these positive effects were most pronounced for adults 60 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(53 reference statements)
0
1
0
1
Order By: Relevance
“…For example, time spent on domestic activities increased with age, and people aged 15 to 24 years tended to spend the least time on these activities (ABS, 2008). Another study by Ricon, Weissman, and Demeter (2013) found that adults aged 55 years and above were more likely to maintain existing activity patterns, particularly for leisure activities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, time spent on domestic activities increased with age, and people aged 15 to 24 years tended to spend the least time on these activities (ABS, 2008). Another study by Ricon, Weissman, and Demeter (2013) found that adults aged 55 years and above were more likely to maintain existing activity patterns, particularly for leisure activities.…”
Section: Discussionmentioning
confidence: 99%
“…No estudo realizado com idosos para avaliar o engajamento em atividades no futuro, identificou-se que as pessoas idosas tendem a manter as atividades em que se envolveram no presente ou no passado, e a não planejar novas (Ricon et al, 2013), corroborando com os dados apontados nesta pesquisa, na qual observou-se apenas um pequeno quantitativo (10,17%) de participação em novas atividades, o que pode ser explicado pela constituição dos hábitos ao longo da vida, esses constituem padrões de comportamento de aprendizagem e organizam rotinas no cotidiano, em alguns casos as pessoas tendem a se apegar a eles, o que limita suas possibilidades de novos aprendizados. Logo, o desenvolvimento relativamente estável de hábitos e papéis ao longo da vida, em diferentes áreas ocupacionais do idoso, tende a fortalecer a manutenção da habituação, ou seja, na pessoa idosa o engajamento em novas atividades é menos evidente (Kielhofner, 2011).…”
Section: Discussionunclassified